O exercício físico é capaz de melhorar expressão de AMPK e GLUT4 em músculo esquelético de ratos alcoolistas e/ou tabagistas - Florido Neto, Armando Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Alcohol and cigarettes are the lawful psychoactive drugs more consumed in the world, usually being consumed in association. Metabolic alterations are linked to alcohol consumption and tobacco use involving impairment in the expression of proteins related to cellular metabolism. The objective of this study was to evaluate if the regular physical exercise can promote positive effects on the possible impairment related to expression of GLUT4 and AMPK in the skeletal muscle of smoker and/or alcoholic rats. Eighty Wistar rats were divided into 8 groups C:control, S:smoker, A:alcoholic, SA: smoker alcoholic, CE: control exercised, SE: smoker exercised, AE: alcoholic exercised, SAE: smoker alcoholic exercised. Smoker groups were exposed to combustion of four cigarettes, 1h a day, 2x a day, 5x a week for 2 months. A mixture of 10% v/v of ethanol plus water was offered to alcoholic groups. Exercised groups were trained on a treadmill (vel=10 m/min) 5x a week, 1h a day, during two months. Insulin Tolerance Test, Glucose Test tolerance were performed for the insulin sensitivity evaluation. RT-PCR was used for quantification of genes Slc2a4 (codes GLUT4) and Prkaa2 (codes AMPK). Western blotting was used for protein content (GLUT4 and AMPK) analysis. One-way Anova and Student t-test were used to analyze the statistical differences among the groups. P values less than 5% were considered significant. S, A and SA groups showed a reduction in body weight (P< 0.05), and SE, AE and SAE groups showed a normal weight gain compared to the others...

Álcool e cigarro são as drogas psicoativas lícitas mais consumidas no mundo, sendo na maioria das vezes, consumidas em associação. Alterações metabólicas estão associadas com consumo de álcool e cigarro, envolvendo prejuízos na expressão de proteínas envolvidas no metabolismo celular. O objetivo do presente estudo foi avaliar se a prática regular de exercício físico pode ter efeitos positivos sobre possíveis alterações encontradas na expressão de proteínas do metabolismo celular, GLUT4 e AMPK, em músculo esquelético de ratos tabagistas e/ou alcoolistas. Foram utilizados 80 ratos Wistar, divididos em 8 grupos C: controle, F: fumante, A: alcoolista, FA: fumante alcoolista, CE: controle exercitado, FE: fumantes exercitado, AE: alcoolista exercitado, FAE: fumantes alcoolista exercitado. Grupos de fumantes foram expostos à combustão de quatro cigarros, 1h/dia, 2x/dia, 5x/semana durante 60 dias. Uma mistura de 10% v/v de etanol absoluto e água foi oferecida aos grupos alcoolistas. Grupos exercitados realizaram treinamento em esteira 5x/semana, 1h/dia, 10m/min, durante 60 dias. Teste de Tolerância à insulina, Teste de Tolerância a Glicose foram realizados para avaliação da sensibilidade à insulina.RT-PCR foi utilizada para a quantificação dos genes Slc2a4 (GLUT4) e Prkaa2 (AMPK) e para a quantificação do conteúdo proteico de GLUT4 e AMPK foi usada a técnica de Western blotting...
Keywords: Fisioterapia; Álcool; Fumo; Exercicio isometrico; Insulina; Musculos; Physical therapy